The Sympathizer - Nguyen, Viet Thanh 1971- (New York : Grove Press, 2016)
Follows a Viet Cong agent as he spies on a South Vietnamese army general and his compatriots as they start a new life in 1975 Los Angeles.
The story of a South Vietnamese captain -- a man brought up by an absent French father and a poor Vietnamese mother, a man who went to university in America -- who returns to Vietnam to fight for the Communist cause.
"Grove Press; Reprint edition (April 12, 2016)"-- Amazon.com.
Keywords: Vietnamese -- California; Los Angeles; Soldiers -- Vietnam (Republic); Fiction; Communists -- Vietnam (Republic); Fiction; Vietnam War, 1961-1975 -- Fiction; Vietnam (Republic) -- Vietnam War, 1961-1975; Fiction; Fiction; Historical fiction; Spy stories; Spy stories; Historical fiction; Spy fiction; Spy stories; Historical fiction